Impact of aging on allergy and mucosal immunity in upper respiratory tract - Seyyed Abbas Hashemi; Seyyed Abdollah Madani; Saied Abediankenari (Al Ameen Medical College, 2016)
Objectives: Although age-associated alterations on immune system are well described and aging is a subject of different investigations but studies did not discuss about the effect of advanced age on immunity in upper respiratory tract disorders. Therefore in this trial, we elucidated how aging imposes allergic reactions and mucosal immune responses mediated by salivary IgA and serum Total IgE in patients suffered from upper respiratory tract diseases. Study Design: Experimental study. Place and Duration of Study: Department of Otorhinolaringology, microbiology and immunology, Mazandaran university of medical sciences, sari, Iran, from September 2010 to august 2011. Methods: In this study, 140 patients in 7 age groups with upper respiratory tract infections underwent salivary IgA assessment by direct immunoenzymatic determination and serum Total IgE by enzyme linked immunoabsorbent assay. We compared each study arm to the youngest subjects. Results: There was no significant difference in salivary IgA level for patients younger than 60 but a significant change observed for patients older than 60 (p=0.01). Likewise, there was no significant change for total IgE. Conclusion: This research didn't provide any evidence about the minus impact of aging on allergic reactions in upper respiratory tract infections .There was an up regulation in mucosal immunity mediated by salivary IgA in patients aged over sixty which revealed secretory IgA plays an important role in mucosal defense of aged subjects.